2005
DOI: 10.1002/adma.200500885
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Tungsten Oxide Nanowire Networks

Abstract: Among transition metal oxides, tungsten oxides (WO 3±d )are of great interest and have been investigated extensively owing to their promising physical and chemical properties.[1±6] With outstanding electrochromic, optochromic, and gaschromic properties, tungsten oxides have been used to construct flatpanel displays, photoelectrochromic ªsmartº windows, optical modulation devices, write±read±erase optical devices, gas sensors, humidity and temperature sensors, and so forth.[1±5]Recently, some non-stoichiometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
264
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(281 citation statements)
references
References 29 publications
14
264
1
2
Order By: Relevance
“…15͒ or WO 3 . 16 The degree of the networking, by sintering in the intersection of the nanowires, and the thickness of the network were found to increase with the duration of the deposition. 15 Nanowire networks with thicknesses in the range of tens of microns have potential applications related to their high surface area.…”
Section: Resultsmentioning
confidence: 95%
“…15͒ or WO 3 . 16 The degree of the networking, by sintering in the intersection of the nanowires, and the thickness of the network were found to increase with the duration of the deposition. 15 Nanowire networks with thicknesses in the range of tens of microns have potential applications related to their high surface area.…”
Section: Resultsmentioning
confidence: 95%
“…It can be concluded that the growth direction of WO x NRs was along the [010] direction. Streaks are observed in the FFT pattern (Figure 5b, inset) which were perpendicular to [010], which can be attributed to planar defects within the NRs caused by oxygen vacancies [22]. The presence of planar oxygen vacancies perpendicular to the growth direction [010] could suppress the growth along e.g.…”
Section: Characterizationmentioning
confidence: 99%
“…The most important feature of sensor based on WO 3 nanowires is that their response is not affected by the extent of humidity. Diverse forms of WO 3 nanowires such as monoclinic [18], hexagonal [19], and cubic [20] have recently been synthesized by adopting different methodologies. Various methods such as electrochemical deposition, electroless deposition, electrophoretic deposition, template filling, sol-gel method, and pressure injection techniques have been employed for the fabrication of tungsten trioxide on template.…”
Section: Introductionmentioning
confidence: 99%